A double-blind placebo-controlled study of brexpiprazole for the treatment of borderline personality disorder. (February 2022) - Grant, Jon E.; Valle, Stephanie; Chesivoir, Eve; Ehsan, Dustin; Chamberlain, Samuel R.
Abstract : Background: Borderline personality disorder is associated with impaired quality of life and has a number of untoward public health associations. There is no established first-line pharmacological treatment for borderline personality disorder, and available options are not suitable for all individuals. Aims: To evaluate brexpiprazole, which has effects on the dopaminergic and serotonergic systems, for the reduction of borderline personality disorder symptoms. Method: Eighty adults with borderline personality disorder were recruited for a randomised, double-blind placebo-controlled study. Participants received 12-week treatment with brexpiprazole (1 mg/day for 1 week, then increasing to 2 mg/day) or placebo in a parallel design. The primary efficacy outcome measure was the clinician-rated Zanarini Rating Scale for Borderline Personality Disorder (ZAN-BPD). Safety data were collected. Effects of active versus placebo treatment were characterised with linear repeated measures models. Results: There was a significant interaction between treatment and time on the ZAN-BPD scale ( P = 0.0031), solely because of differentiation specifically at week 12. Brexpiprazole was generally well tolerated. Secondary measures did not result in statistically significant differences from placebo. Conclusions: Brexpiprazole appears to have some possible effect on borderline personality disorder symptoms, but further studies are needed because of the significant effects evident, specifically at the final time point. These findings also need to be viewed cautiously, given the small sample size, large drop-out rate and robust placebo response.